In Vitro Schistosomicidal Activity of Some Brazilian Cerrado Species and Their Isolated Compounds. (8th August 2012) - Cunha, Nayanne Larissa; Uchôa, Camila Jacintho de Mendonça; Cintra, Lucas Silva; Souza, Herbert Cristian de; Peixoto, Juliana Andrade; Silva, Claudia Peres; Magalhães, Lizandra Guidi; Gimenez, Valéria Maria Meleiro; Groppo, Milton; Rodrigues, Vanderlei; da Silva Filho, Ademar Alves; Andrade e Silva, Márcio Luís; et al.
Abstract : Miconia langsdorffii Cogn. (Melastomataceae), Roupala montana Aubl. (Proteaceae), Struthanthus syringifolius (Mart.) (Loranthaceae), and Schefflera vinosa (Cham. & Schltdl.) Frodin (Araliaceae) are plant species from the Brazilian Cerrado whose schistosomicidal potential has not yet been described. The crude extracts, fractions, the triterpenes betulin, oleanolic acid, ursolic acid and the flavonoids quercetin 3- O - β -D -rhamnoside, quercetin 3- O - β -D -glucoside, quercetin 3- O - β -D -glucopyranosyl-(1-2)- α -L -rhamnopyranoside and isorhamnetin 3- O - β -D -glucopyranosyl-(1-2)- α -L -rhamnopyranoside were evaluated in vitro against Schistosoma mansoni adult worms and the bioactive n -hexane fractions of the mentioned species were also analyzed by GC-MS. Betulin was able to cause worm death percentage values of 25% after 120 h (at 100 μ M), and 25% and 50% after 24 and 120 h (at 200 μ M), respectively; besides the flavonoid quercetin 3- O - β -D -rhamnoside promoted 25% of death of the parasites at 100 μ M. Farther the flavonoids quercetin 3- O - β -D -glucoside and quercetin 3- O - β -D -rhamnoside at 100 μ M exhibited significantly reduction in motor activity, 75% and 87.5%, respectively. Biological results indicated that crude extracts of R. montana, S. vinosa, and M. langsdorffii and some n -hexane and EtOAc fractions of this species were able to induce worm death to some extent. The results suggest that lupane-type triterpenes and flavonoid monoglycosides should be considered for further antiparasites studies.